AGE AND ORIGIN OF ALBIAN GLAUCONITES AND ASSOCIATED CLAY MINERALS INFERRED FROM A DETAILED GEOCHEMICAL ANALYSIS - Rousset D.; Clauer N.; Leclerc S.; Lancelot J.; Cathelineau M.; Aranyossy J.-F. (My University, 2004)
Glauconitic grains are abundant in sandstones and siltstones from Albian and Cenomanian (transition between Lower and Upper Cretaceous) formations of southeastern France. Morphological and crystal-chemical data show that the "green grains" can be considered as glauconite s.s., with minute amounts of pyrite, dolomite, calcite, and other clay minerals as grain coatings or crack fillings. Glauconite grains formed early during sedimentation, generally from detrital chlorite, biotite, or clay particles, and were found scattered together with other detrital mineral phases (muscovite, quartz) in the silt, in which porosity was considerably reduced afterwards by four stages of carbonate (calcite, dolomite) cementation. Geochemical data, especially the Fe, U, and Ce contents of the glauconitic grains, strongly suggest increasing oxidizing conditions with time in the sedimentation environment. The detailed geochemical analyses also allow the pristine glauconite grains to be distinguished from the other clay minerals occurring in the sequence. This enabled K-Ar and Rb-Sr dating of the glauconitic material, which yields identical results of 97.9 +/- 0.4 and 97.9 +/- 3.5 Ma, respectively. These dates point to a synsedimentary origin for the glauconites during the Late Albian (about 97-98 Ma). The K-Ar data also indicate that the Albian-Cenomanian boundary should be placed at 96.0 +/- 1.9 Ma. The similarity between the K-Ar and Rb-Sr ages precludes any further significant pervasive recrystallization of these minerals during burial of the sequence either by beat flux or fluid flow. The K-Ar study of the clay matrix from the same siltstones suggests synsedimentary precipitation of additional clay minerals, probably together with the glauconite grains, such as mixed-layer illite-smectite identified in the clay size fraction of the sedimentary succession.
Keywords: Glauconite; Mesozoic::Cretaceous::Upper::Cenomanian; Мезозой::Меловая::Нижний::Альбский; Мезозой::Меловая::Верхний::Сеноманский; Mesozoic::Cretaceous::Lower::Albian